Mapping Multi Stakeholder Roles on Fire Management in Conservation Areas of Kuningan Regency - Indriani Ekasari; Ronggo Sadono; Djoko Marsono; Joko Ridho Witono (Jurnal Manajemen Hutan Tropika, 2020)
Forest fire was a persistent concern management in conservation areas of Mount Ciremai National Park (MCNP) and Kuningan Botanical Garden (KBG). Many of the forest fire was sparked by anthropogenic ignitions like careless fire use for extracting forest honey. This study aims to map multi stakeholder roles on fire management in conservation areas. Twenty-seven actors were interviewed to learn who are the fire actors and network. These multi stakeholders included government officials, local businessmen, non-governmental organizations and community members. Study site and data collection were carried out in seven villages around conservation areas from July to September 2019. The relationships between the actors were analyzed with the software Node XL Basic and Gephi 9.0.2 using the Social Network Analysis. Our results identify close relationships and strong connections to all actors of more than half (63.2%) but social or personal approach between all actors were still required. Head of MCNP, Head of KBG and Head of AKAR (Aktivitas Anak Rimba) acted as the important actors. To prevent the area from further fire occurrences, management authorities should establish mutual confidence and make other actors believe that heads of conservation areas are a solid team to prevent conservation areas from burning.